Penyelesaian Kredit Macet dengan Benda Jaminan Fidusia yang Dipalsukan (Studi Kasus: PT. BPR. Ulatidana Rahayu) - Ni Made Sintia Tarisa; I Nyoman Putu Budiartha; Ni Made Sukaryati Karma (Fakultas Hukum, Universitas Warmadewa, 2020)
An agreement is a legal action carried out by two or more people who have legal consequences for the rights and obligations of the makers. The agreement involves at least 2 or more people. In addition to individuals, the parties to the agreement may also consist of legal entities. Limited Liability Company (PT) is a legal entity that is one of the parties or both of them in the agreement. Both are legal subjects who can carry out legal actions and carry out their rights and obligations. Referring to the above problems, this study was conducted with the aim of describing how the legal protection of bank creditors in granting credit with fiduciary collateral objects falsified and how the legal consequences if the debtor commits the fraud of the BPKB (certificate of ownership of motor vehicles) credit guarantee. This research was designed using an empirical research approach. The results of this study indicated that the legal protection of bank creditors in falsifying collateral loans with fiduciary collateral objects is regulated in articles 1131 and 1132 of the Civil Code. Other legal protection given to creditors is preventive legal protection which is legal protection to prevent disputes and in this case concerning the rights and obligations of creditors. Another result of this research is the debtor who falsified the collateral object or the BPKB of the vehicle that was used for credit guarantees was used in article 263 of the Criminal Code with the threat of a maximum prison sentence of six years. So, legal protection and sanctions to creditors and debtors, if a problem occurs is regulated in statutory regulation.